Changes induced by estradiol-ethylenediamine derivative on perfusion pressure and coronary resistance in isolated rat heart: L-type calcium channel - Valverde, Lauro Figueroa; Cedillo, Francisco Diaz; Ramos, Maria Lopez; Cervera, Elodia Garcia; Quijano, Karen; Cordoba, Johani (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
AIM: The present study was designed to investigate the effects of estradiol-ethylenediamine derivative on perfusion pressure and coronary resistance in rats. An additional aim was to identify the molecular mechanisms involved. METHODS: The Langendorff model was used to measure perfusion pressure and coronary resistance changes in isolated rat heart after estradiol-ethylenediamine derivative alone and following compounds; tamoxifen (estrogen receptor antagonist), prazosin (alpha1 adrenoreceptor antagonist), metoprolol (selective beta1 receptor blocker), indomethacin (prostanglandin synthesis inhibitor) and nifedipine (L-type calcium-channel inhibitor). RESULTS: The results show that estradiol-ethylenediamine derivative [10(-9) mmol] significantly increased perfusion pressure (p = 0.005) and coronary resistance (p = 0.006) in isolated rat heart. Additionally, the effect of estradiolethylenediamine on perfusion pressure [10(-9) to 10(-4) mmol] was only blocked in the presence of the L-type calcium-channel (nifedipine). CONCLUSIONS: These data suggest that the effect of estradiol-ethylenediamine on perfusion pressure and vascular coronary involves activation of the L-type calcium channel through a non-genomic molecular mechanism.
Keywords: Animals; koronární cirkulace; antagonisté estrogenu; Female; Ethylenediamines; Cyclooxygenase Inhibitors; Rats, Wistar; tamoxifen; ženské pohlaví; estradiol; In Vitro Techniques; vápníkové kanály - typ L; indomethacin; Nifedipine; techniky in vitro; Indomethacin; blokátory kalciových kanálů; Calcium Channels, L-Type; nifedipin; Vascular Resistance; Metoprolol; prazosin; krevní tlak; cévní rezistence; alfa-1-adrenergní receptory - antagonisté; Coronary Circulation; Estrogen Antagonists; Adrenergic beta-1 Receptor Antagonists; metoprolol; Calcium Channel Blockers; inhibitory cyklooxygenasy; antagonisté beta-1-adrenergních receptorů; krysa rodu Rattus; Adrenergic alpha-1 Receptor Antagonists; Tamoxifen; zvířata; Estradiol; Prazosin; Blood Pressure; Myocardium; myokard; Rats; ethylendiaminy; potkani Wistar